Answer:
Hence,the average rate of change for this quadratic function for the interval from x = 0 to x = 2 is:
-2
Explanation:
The average rate of a function f(x) from x=a to x=b is given as:
![=(f(b)-f(a))/(b-a)](https://img.qammunity.org/2019/formulas/mathematics/college/98px20o6ul3xbdlyobcy7gjbd0tjg93zyw.png)
Clearly we are asked to find the average rate of change from x=0 to x=2.
i.e. a=0 and b=2
Also, from the graph it could be observed that:
f(0)=1
and f(2)=-3
Hence, the average rate of change is calculated as:
![=(f(2)-f(0))/(2-0)\\\\=(-3-1)/(2-0)\\\\=(-4)/(2)\\\\=-2](https://img.qammunity.org/2019/formulas/mathematics/college/vjc64841faqt20kb6ydzj11clrs5fi634h.png)
Hence,the average rate of change for this quadratic function for the interval from x = 0 to x = 2 is:
-2